Optimization of Student Loyalty through Rewards and Students’ Satisfaction as Intervening Variables - Durahman Marpaung; Prianda Pebri; Nirmalasari Nirmalasari; Srie Hartati; Nasib Nasib (Budapest International Research and Critics University, 2021)
STIE Muhammadiyah Asahan is a private university under the supervision of Regional 1 Education Service Institution (LL Dikti Wilayah 1). This study aims to determine the Optimization of Student Loyalty through Rewards and Students’ Satisfaction as Intervening Variables. The research approach used in this research is quantitative. Data obtained by distributing questionnaires with a Likert scale. The questionnaire is arranged based on indicators of reward, satisfaction and loyalty. The target population in this study are 71 students for the 2017-2018 academic year. The sampling technique uses saturated samples. So that 71 respondents are selected to be the sample. Data analysis uses path analysis to determine the direct and indirect effect of the reward variable on student loyalty through student satisfaction. The results of the research that can be drawn 1) Rewards have a significant effect on student satisfaction at STIE Muhammadiyah Asahan. 2) Reward has no effect on student loyalty at STIE Muhammadiyah Asahan. 3) Student satisfaction has a significant effect on student loyalty at STIE Muhammadiyah Asahan.. 4) Reward has a significant effect on student loyalty through student satisfaction at STIE Muhammadiyah Asahan.